Efektivitas Program Kartu Tani di Desa Penambuhan, Kecamatan Margorejo, Kabupaten Pati - Ramadhani, Devia Isna; Prayoga, Kadhung; Siwi Gayatri, Siwi Gayatri (Universitas Galuh, 2025)
The Farmer Card program was designed to improve farmers’ welfare and strengthen the agricultural sector. Evaluating the program’s effectiveness was important because it served as a key access point for farmers to agricultural resources. This study aimed to (1) identify the level of effectiveness of the Farmer Card program and (2) analyze factors that influenced its effectiveness in Penambuhan Village, Margorejo District, Pati Regency. The research was conducted from September to October 2024. The survey method was used, with samples selected through proportional random sampling. Quantitative data analysis was applied. Independent variables included farmers’ age, knowledge, availability of facilities and infrastructure, participation, and the role of extension workers. The dependent variable was the program’s effectiveness. The results showed that the Farmer Card program in Penambuhan Village ran effectively. However, the dimension measuring program success was categorized as less effective, while target achievement and satisfaction were in the effective category. Farmers’ age, knowledge, availability of facilities and infrastructure, participation, and extension workers’ roles simultaneously influenced the program’s effectiveness. Partially, farmers’ knowledge, facilities and infrastructure, and participation affected effectiveness, while age and extension workers’ roles did not. The study recommended that extension workers provide socialization and assistance to farmers about the Farmer Card program beyond subsidized fertilizers, including business credit applications, saving, and direct sales of harvests. Creating a WhatsApp group was also suggested to facilitate communication between farmer groups and extension workers.